Uncertainty and Track Stability: Analysis of Partial Safety Factors for High-Speed Railway Bridges - António Abel Henriques (2022)
Short-span railway bridges subjected to high-speed traffic are structures where dynamic effects are mandatory. Additionally, the variability associated with materials and geometric characteristics introduces uncertainty to the safety assessment of railway traffic. This work discusses the current norms limit for vertical deck acceleration regarding the evaluation of stability on ballasted tracks, as stated on Annex A2 of EN1990. A probabilistic methodology to define a partial safety factor is presented, employing dynamic analyses and Monte Carlo simulations. The evaluation of a case study is presented for a single-span filler-beam bridge of the Portuguese Railways Network. The results allow the definition of deterministic design scenarios that are compared to the simulations outcome. Conclusions show consistent partial safety factors with the norms limit, contributing to further discussion of this factor. (c) 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.